Handling policies for Italian existing bridges with a territorial approach: the case study of Caserta, Italy. (February 2023) - Zizi, Mattia; Bencivenga, Pasquale; De Matteis, Gianfranco
Abstract: The present manuscript deals with the huge problem related to the structural safety of the Italian infrastructural asset. The case study of the Province of Caserta, whose infrastructural heritage includes about 900 in-service bridges mainly realized in the second half of the last century, is presented and addressed. In this territorial context, a wide handling activity started since 2017, including: i. census of all structures; ii. definition of a priority scale for programming in-situ inspections; iii. visual inspections aimed at estimating the conservation state of the structures and identifying structural issues; and iv. definition of provisions for the structural safety of existing bridges. Hence, the investigated sample is presented, firstly. Then, given the large number of structures of interest, an empirical methodology for defining a priority scale for the in-situ surveys is proposed. Based on such a procedure, the outcome of the inspections related to 60 bridges are analyzed and discussed and the main structural issues affecting the considered bridges highlighted.